Pengaruh Kompetensi, Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai dengan Motivasi sebagai Variabel Intervening - Ezzah Nahrisah; Manullang , Bunga Juwita Martauli; Alvin Fahlevi; Suginam (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
The main objective of this study is to determine whether motivation mediates the influence of competence, human resource development on employee performance. Questionnaires and interviews were used to collect data. With a sample size of 138, the participants in this study were all employees of the North Sumatra Province Transportation Service. This type of research is associative quantitative, data collection was carried out by distributing questionnaires and then processing the data using the SPSS Version 25 tool. The research location was at the Department of Transportation of North Sumatra Province. The results mean that the content has a positive and significant effect on work motivation, meaning that every time the load increases, work motivation also increases, if there is a decrease in the load on work motivation, it will decrease significantly. Income has a positive and significant effect on work motivation. HR development has a positive and significant effect on work motivation. Competence has a positive and significant effect on employee performance. HR development has a positive and significant effect on employee performance. Work motivation has a positive effect on employee performance. Work motivation is able to influence competence indirectly on employee performance. Work motivation can indirectly influence HR development on employee performance.